The interactive use of augmented reality for educating the elderly on common age-related eye disease - Yuet Yi Hung; Wang Yee Chu; Juming Jiang; Wing Yiu Yeung; Wing Huen Yan; Tai On Kwok; Yau Kei Chan (BMC Geriatrics)
Abstract Background The prevalence of age-related eye disorders is increasing with the aging of the global population. Community-based visual health education for the elderly has become a crucial intervention. With the advancement of technology, the application of extended reality (XR), such as virtual reality (VR) and augmented reality (AR), in health education has become more popular. This study aims to assess the effectiveness of educating the elderly about common age-related eye disorders through a novel AR-based health education workshop. Methods An AR-based education workshop was designed for the elderly to understand the major visual symptoms of several eye diseases and experience the challenges faced by visually impaired people. The effectiveness of the workshop was assessed by conducting pre- and post-activity surveys to measure the knowledge acquisition of the participants from this workshop. Results The intervention was found to significantly improve knowledge of age-related eye diseases among the elderly, while the participants’ age and education level could influence the effectiveness of their knowledge gained from the workshop. Conclusions Our study revealed the potential of the use of AR technology in facilitating health education on eye diseases in the elderly. The specific backgrounds and characteristics of target participants and the combination of AR with other pedagogical approaches warrant further investigation to maximize the impact of AR-based workshops in health education in broader healthcare contexts.